Pilot-project comparison of microbial water quality changes within continuous water supply and intermittent water supply - Khoo, Jun Sean (Nanyang Technological University, 2022)
With global warming persisting, international interest shifted from continuous water supply (CWS) towards intermittent water supply (IWS) to ameliorate water management. Understanding the impact of hydraulic movement within drinking water distribution systems (DWDS) is vital for supplementing potable water. This research seeks to evaluate water supplied from both IWS and CWS side-by-side and compare physio-chemically water samples and microbial counts present within samples. Samples were collected in three cycles over three months. Flow cytometry was utilized to quantify the heterogeneous population of cells based on the genome constitution. Microbial communities were observed with more significant counts within IWS, where stagnant water was prevalent. Dissimilarities in microbial community were observed with CWS-fast with IWS-fast, and occasional CWS-slow and IWS-fast conditions.. Physico-chemical parameters correlated to microbial counts, where monochloramine, nitrite, and nitrate significantly differed from inlet conditions. Stagnation has resulted in weaker rigidity in biofilm, where more detachment was observed with IWS with transients of nitrous groups within the first 90 seconds of sampling. This study concludes that IWS has significantly lower water quality and differences in bulk water microbial community compared to CWS. However, with a further understanding of microbial species present for water quality regulation or the introduction of probiotics, IWS could be employed safely for the DWDS.